A Study on the English Learning Difficulties Faced by Low Achiever Students at SMA Negeri 7 Bulukumba - Nurul Latifa Amin; Muhammad Tahir; Muhammad Arham Basri (International Journal of Language, Education, and Literature, 2025)
This study analyzes the difficulties faced by low achiever students in learning English at SMA Negeri 7 Bulukumba. Focusing on two research questions, the study aims to (1) identify the causes of low achievement in English learning and (2) explore the perceptions of both students and teachers, particularly related to the use of technology. This qualitative case study involved five eleventh-grade low achiever students and two English teachers. Data were collected through interviews, observations, and documentation. Findings show internal factors such as low motivation, limited vocabulary, and poor grammar mastery hinder learning. Externally, the lack of family support, teacher-centered methods, and unproductive technology use compound these issues. While digital tools could aid learning, students’ low digital literacy and teachers’ limited technological integration reduce their impact. The study recommends personalized instruction, increased teacher support, and infrastructure improvements to address these challenges.